Stepped water isotherm and breakthrough curves on aluminium fumarate metal–organic framework: experimental and modelling study - Bozbiyik, Belgin; Van Assche, Tom; Lannoeye, Jeroen; De Vos, Dirk E.; Baron, Gino V.; Denayer, Joeri F. M. (Adsorption : journal of the International Adsorption Society, 2017)
Adsorption of water vapour on the Al-fumarate metal–organic framework (MOF) was studied in static and dynamic conditions, by performing gravimetric and fixed bed experiments. A two-step, type IV water isotherm is obtained, which reveals the complexity and the duality of the hydrophilic/hydrophobic behaviour of this MOF. Breakthrough experiments with feed conditions corresponding to three different zones in the water adsorption isotherm were performed to study the effect of isotherm shape on the column dynamics. At low partial pressure of water in the feed, a single breakthrough step is observed while a stepped profile is observed at higher partial pressure of water. These breakthrough curves could be described qualitatively with a simple model accounting for the isotherm shape.